The Impact of E-Service Quality on Customer Satisfaction and Consumer Engagement Behaviors Toward Traveloka - Rumondang Sianipar, Gracia Angelica; Simanjuntak, Mariana (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
In this digital era, online booking platforms such as Traveloka are becoming increasingly popular. Electronic service quality (e-service quality) is an important factor influencing customer satisfaction and encouraging positive engagement behavior on the platform. This research aims to analyze the influence of e-service quality on customer satisfaction and consumer engagement behavior at Traveloka. Research data was collected through an online survey of 35 Traveloka users in Indonesia. The research results show that e-service quality has a positive influence on customer satisfaction and consumer engagement behavior at Traveloka. Customer satisfaction has also been proven to mediate the relationship between e-service quality and consumer engagement behavior. These findings indicate that Traveloka needs to continue to improve the quality of its e-services to increase customer satisfaction and encourage positive engagement behavior. This research provides theoretical and practical contributions in understanding the influence of e-service quality on customer satisfaction and consumer engagement behavior at Traveloka. The findings of this research can help Traveloka develop appropriate strategies to improve the quality of its electronic services and achieve a competitive advantage in the market.